2007
DOI: 10.1093/rheumatology/kem091
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of adalimumab for rheumatoid arthritis in patients with a history of TNF-antagonist therapy in clinical practice

Abstract: In typical clinical practice, adalimumab was effective and well-tolerated in patients with RA previously treated with etanercept and/or infliximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
120
1
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(150 citation statements)
references
References 32 publications
18
120
1
11
Order By: Relevance
“…From course 2 onward, the dropout rate was about 10% for all subsequent courses, a value consistent with that reported for other biologic therapies 4,5,6 . We agree with Dr. Abeles that knowing the number of dropouts due to insufficient response is important.…”
Section: Dr Keystone Et Al Replysupporting
confidence: 85%
“…From course 2 onward, the dropout rate was about 10% for all subsequent courses, a value consistent with that reported for other biologic therapies 4,5,6 . We agree with Dr. Abeles that knowing the number of dropouts due to insufficient response is important.…”
Section: Dr Keystone Et Al Replysupporting
confidence: 85%
“…In the Research in Active Rheumatoid Arthritis Trial (ReAct), a large, 12-week, open-label study of adalimumab involving 899 patients with a history of etanercept and/or infliximab therapy, adalimumab treatment was effective, with 60% of patients achieving an ACR20 response and 33% experiencing an ACR50 response 21 . In an ongoing 5-year postmarketing observational study (ReAlise) of patients who had completed ReAct, among 408 of 3433 who were TNF-antagonist-experienced, 77% had achieved ACR20 and 53% had achieved ACR50 by 3 years of adalimumab therapy 22 24 .…”
Section: Rheumatologymentioning
confidence: 99%
“…The results of controlled clinical trials and open studies demonstrated that subcutaneous administration every two weeks of the drug is safe and effective in adult patients with rheumatoid and psoriatic arthritis [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], as well as in children with juvenile idiopathic arthritis and uveitis [49][50][51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%